Flexibilidade na utilização de diesel ou biodiesel: uma abordagem utilizando a teoria de opções reais - Ferreira, Leonardo Leandro (2007)
This paper will point the development of Biodiesel as a renewable fuel on brazilian energy matrix. Specially pointing the flexibility of utilization either of Biodiesel or traditional petroleum originated Diesel. The valuation of the flexibility of a diesel cycle engine that could switch by Diesel or Biodiesel, will be done. The valuation of this operational flexibility will be done with Real Options Theory. By the end will be done comments of the aggregate value added to a country like Brazil, which have a transport sector mainly focused in diesel fueled vehicles.